Burning urban cities of South Africa due to civil turmoil 2021: Socio-economic and environmental consequences - (:unkn) unknown (My University, 2022)
A violent outbreak of civil unrest (Jul 7–19, 2021) triggered immediately after the incarceration of the formerSouth African president claimed 337 lives and brought disruptive damages to societal movements, environment,and COVID-19 containment measures. The present work aimed to analyze the hotspots of fire sites, its significanceson societal activities, air quality and COVID-19 pandemic using ground based and geospatial data. Theresults revealed steady rise in air pollution levels all through the region due to increase in fire activities. Positiveinfluence on the regional air quality was observed to be high than the limits set forth by WHO. The daily meanvalues of PM2.5 (62.37–104.34 μg/m3) and PM10 (108.86–156.78 μg/m3) presented potential short and long-termrisks to public health. Similarly, COVID-19 cases also increased during the social unrest period even when thecommunity mobility was less than the normal conditions. This type of cost benefit analysis proves to provideevidence of deteriorating air quality and aids to examine the adverse impacts on human health during the globalpandemic.
Keywords: African Research